The National Surgical Quality Improvement Program 30-Day Challenge: Microsurgical Breast Reconstruction Outcomes Reporting Reliability - Austin D. Chen; Parisa Kamali, MD; Anmol S. Chattha, BA; Alexandra Bucknor, MBBS, MSc; Justin B. Cohen, MD, MHS; Patrick P. Bletsis, BSc; Renata Flecha-Hirsch, BA; Adam M. Tobias, MD; Bernard T. Lee, MD, MBA, MPH; Samuel J. Lin, MD, MBA (Plastic and Reconstructive Surgery, Global Open, 2018)
Background:. The aim was to assess reliability of the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) 30-day perioperative outcomes and complications for immediate, free-tissue transfer breast reconstruction by direct comparisons with our 30-day and overall institutional data, and assessing those that occur after 30 days. Methods:. Data were retrieved for consecutive immediate, free-tissue transfer breast reconstruction patients from a single-institution database (2010–2015) and the ACS-NSQIP (2011–2014). Multiple logistic regressions were performed to compare adjusted outcomes between the 2 datasets. Results:. For institutional versus ACS-NSQIP outcomes, there were no significant differences in surgical-site infection (SSI; 30-day, 3.6% versus 4.1%, P = 0.818; overall, 5.3% versus 4.1%, P = 0.198), wound disruption (WD; 30-day, 1.3% versus 1.5%, P = 0.526; overall, 2.3% versus 1.5%, P = 0.560), or unplanned readmission (URA; 30-day, 2.3% versus 3.3%, P = 0.714; overall, 4.6% versus 3.3%, P = 0.061). However, the ACS-NSQIP reported a significantly higher unplanned reoperation (URO) rate (30-day, 3.6% versus 9.5%, P < 0.001; overall, 5.3% versus 9.5%, P = 0.025). Institutional complications consisted of 5.3% SSI, 2.3% WD, 5.3% URO, and 4.6% URA, of which 25.0% SSI, 28.6% WD, 12.5% URO, and 7.1% URA occurred at 30–60 days, and 6.3% SSI, 14.3% WD, 18.8% URO, and 42.9% URA occurred after 60 days. Conclusion:. For immediate, free-tissue breast reconstruction, the ACS-NSQIP may be reliable for monitoring and comparing SSI, WD, URO, and URA rates. However, clinicians may find it useful to understand limitations of the ACS-NSQIP for complications and risk factors, as it may underreport complications occurring beyond 30 days.